Do ETFs Increase Volatility? - BEN-DAVID, ITZHAK; FRANZONI, FRANCESCO; MOUSSAWI, RABIH (The Journal of finance (New York), 2018)
Due to their low trading costs, exchange-traded funds (ETFs) are a potential catalyst for short-horizon liquidity traders. The liquidity shocks can propagate to the under-lying securities through the arbitrage channel, and ETFs may increase the nonfundamental volatility of the securities in their baskets. We exploit exogenous changes in index membership and find that stocks with higher ETF ownership display significantly higher volatility. ETF ownership increases the negative autocorrelation in stock prices. The increase in volatility appears to introduce undiversifiable risk in prices because stocks with high ETF ownership earn a significant risk premium of up to 56 basis points monthly.